2008
DOI: 10.1016/j.cgh.2007.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Mucosal Immunity Identified in the Colon of Patients With Irritable Bowel Syndrome

Abstract: BACKGROUND & AIMS-Irritable bowel syndrome (IBS) has been associated with mucosal dysfunction,, mild inflammation, and altered colonic bacteria. We used microarray expression profiling of sigmoid colon mucosa to assess whether there are stably expressed sets of genes that suggest there are objective molecular biomarkers associated with IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 43 publications
3
80
0
3
Order By: Relevance
“…Similarly, Chang et al (14) have demonstrated a reduced expression of proinflammatory cytokines in the sigmoid colon of patients with IBS. There are also studies reporting colonic mucosal gene expression indicating compromised mucosal immunity in IBS and the downregulation of genes related to T cells and macrophages (15,16). Taken together, our data indicate the possibility of mucosal immune dysregulation rather than immunoactivation.…”
Section: Ibs Vs Control Groupsupporting
confidence: 53%
“…Similarly, Chang et al (14) have demonstrated a reduced expression of proinflammatory cytokines in the sigmoid colon of patients with IBS. There are also studies reporting colonic mucosal gene expression indicating compromised mucosal immunity in IBS and the downregulation of genes related to T cells and macrophages (15,16). Taken together, our data indicate the possibility of mucosal immune dysregulation rather than immunoactivation.…”
Section: Ibs Vs Control Groupsupporting
confidence: 53%
“…The most important aberrations include visceral hypersensitivity, abnormal gut motility and autonomous nervous system dysfunction, the interactions of which are suggested to make the bowel function susceptible to a number of exogenous and endogenous factors, such as the GI microbiota, diet and psychosocial factors (recently reviewed by Karantanos et al, 2010). In addition, the presence of low-level inflammation in the GI mucosa of IBS patients has also been observed in several studies, including those reported by Aerssens et al (2008), Chadwick et al (2002) and Macsharry et al (2008).…”
Section: Introductionmentioning
confidence: 84%
“…[18][19][20][21][22] Gene expression profiling in tissue samples taken from patients with IBS has been reported using sigmoid colonic mucosal tissue. 23 Although certain gene expression biomarkers have been recently reported in the literature, these markers were derived from data mining of a published inflammatory bowel disease study. 24 However, it is unknown whether there exist 'surrogate' transcriptional biomarkers in peripheral blood cells of patients with IBS.…”
Section: Introductionmentioning
confidence: 99%